Presence of Anti-Glomerular Basement Membrane Antibodies and Myeloperoxidase Anti-Neutrophilic Cytoplasmic Antibodies in a Case of Rapidly Progressive Glomerulonephritis - Mavani, Gaurang P.; Pommier, Max; Win, Sandar; Michelis, Michael F.; Rosenstock, Jordan (Frontiers in Medicine, 2015)
A 69-year-old male had initially presented with low-grade proteinuria, microhematuria, and a positive myeloperoxidase anti-neutrophilic antibody (ANCA). He subsequently developed deterioration of kidney function and developed uremic symptoms. Creatinine was 486.2 μmol/L (5.5 mg/dL). Anti-MPO was positive (titer >8 U, normal <0.4). He was clinically diagnosed with rapidly proliferative glomerulonephritis most likely due to ANCA vasculitis. He received three doses of pulse methylprednisolone therapy. Kidney biopsy showed pauci-immune glomerulonephritis. Immunofluorescence was positive for faint linear IgG staining of glomerular basement membrane (GBM). Anti-GBM antibody was positive 2.1 U (normal <1). He was started on high-dose oral steroids; monthly intravenous cyclophosphamide and plasmapheresis were also initiated. His symptoms improved and creatinine is 247.5 μmol/L (2.8 mg/dL). His repeat anti-GBM antibody was negative. This is a rare case of rapidly progressive glomerulonephritis due to dual MPO-ANCA antibodies and anti-GBM antibodies (DAV).